Phase Ib Study of Combination Therapy with MEK Inhibitor Binimetinib and Phosphatidylinositol 3‐Kinase Inhibitor Buparlisib in Patients with Advanced Solid Tumors with RAS/RAF Alterations. (8th August 2019) - Bardia, Aditya; Gounder, Mrinal; Rodon, Jordi; Janku, Filip; Lolkema, Martijn P.; Stephenson, Joe J.; Bedard, Philippe L.; Schuler, Martin; Sessa, Cristiana; LoRusso, Patricia; Thomas, Michael; Maacke, Heiko; et al.
Abstract: Background: This multicenter, open‐label, phase Ib study investigated the safety and efficacy of binimetinib (MEK inhibitor) in combination with buparlisib (phosphatidylinositol 3‐kinase [PI3K] inhibitor) in patients with advanced solid tumors with RAS/RAF alterations. Materials and Methods: Eighty‐nine patients were enrolled in the study. Eligible patients had advanced solid tumors with disease progression after standard therapy and/or for which no standard therapy existed. Evaluable disease was mandatory, per RECIST version 1.1 and Eastern Cooperative Oncology Group performance status 0‐2. Binimetinib and buparlisib combinations were explored in patients with KRAS‐, NRAS‐, or BRAF ‐mutant advanced solid tumors until the maximum tolerated dose and recommended phase II dose (RP2D) were defined. The expansion phase comprised patients with epidermal growth factor receptor ( EGFR )‐mutant, advanced non‐small cell lung cancer, after progression on an EGFR inhibitor; advanced RAS‐ or BRAF ‐mutant ovarian cancer; or advanced non‐small cell lung cancer with KRAS mutation. Results: At data cutoff, 32/89 patients discontinued treatment because of adverse events. RP2D for continuous dosing was buparlisib 80 mg once daily/binimetinib 45 mg twice daily. The toxicity profile of the combination resulted in a lower dose intensity than anticipated. Six (12.0%) patients with RAS/BRAF ‐mutant ovarian cancer achieved a partial response. Pharmacokinetics of binimetinib were not altered by buparlisib. Pharmacodynamic analyses revealed downregulation of pERK and pS6 in tumor biopsies. Conclusion: Although dual inhibition of MEK and the PI3K pathways showed promising activity in RAS/BRAF ovarian cancer, continuous dosing resulted in intolerable toxicities beyond the dose‐limiting toxicity monitoring period. Alternative schedules such as pulsatile dosing may be advantageous when combining therapies. Abstract : This article reports on the safety and efficacy of binimetinib and buparlisib combination therapy in patients with advanced solid tumors harboring selected genomic alterations in the RAS/RAF pathway.